Globalization as Transition from Traditional Ukrainian Political Values to Worldwide Ones: Measure of Necessity for Ukraine - Mikhalchenko, Mykola; Dashutin, Grygoriy (Filosofiya osvity. Philosophy of Education, 2006)
The peculiarities of transitional processes in the former soviet countries are examined in the context of globalization in the given paper. The Utopian base of liberal project of their development is shown. «Globalization* is determined as a new version of social and Darwinian myth. There are many similarities, including ideological cynicism, between the main globalization tendencies and the processes, which take place in post-soviet countries. Neo-liberal mythology, which ’supplies’ this process ideologically, is based upon three main positions: Deregulation, Privatization and Liberalization. Authors research some aspects of globalization, concerning to the problems of social justice in political, social, ethical and economical spheres.